Up the Bucs: Cultivating Community Identity through Sustainable Placemaking and Sports Architecture in Orlando - Osato, Matteo (University of the Witwatersrand, Johannesburg, 2024)
The research will thoroughly explore the development of the Orlando Football Complex, ex- ploring how cutting-edge technologies, sustainable design principles, and theoretical frame- works can work together to create a vibrant and inclusive footballing hub for the community of Orlando. An architectural principle that will drive the Orlando Football Complex develop- ment is the theory of “placemaking”, where the research will focus on proposing a football precinct that focuses on building spaces that encourage people’s well-being by supporting social interaction, cultural expression and environmental sustainability. The research aims to show what bringing back Orlando Pirates Football Club to Orlando can do for the commu- nity. The Orlando Football Complex aims to create vibrant, accessible and engaging public spaces that create a sense of place and identity in the community of Orlando. This research will examine the architectural context of Orlando, with the goal to develop the project’s objectives of revitalising under-utilised spaces and building new and inclusive spac- es whilst commemorating Orlando’s rich footballing history. The research will discuss how the Orlando Pirates Training Centre and Orlando Pirates Athletes’ Residences on either side of the Orlando Stadium will connect to the already established urban fabric; how the buffer zone can be converted into an urban park, and how pedestrian walkways will connect through the green belt ultimately stitching the sports complex to the existing urban fabric through di- rect and clear sidewalks. It will also explore how urban connection and urban corridors will be utilised in breaking the existing panopticon street system, transforming Orlando East and West into a walkable city with a lively street life. All of this, with the Orlando Football Complex at the heart of it. South Africa’s rich football history and its key role in the apartheid struggle have influenced the intention and design of the Orlando Football Complex. The Complex will stand as a testament to the power of architecture not only to create phys- ical spaces but to cultivate a vibrant and integrated community. The impact that thoughtful architecture and urban planning can have on social cohesion and well-being is profound and will foster a sense of personal and community identity. The envisioned Orlando Football Complex honours the past, embraces the present and shapes a more inclusive future for the legendary neighbourhood of Orlando.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; community; identity, sustainability; placemaking; ootball; SDG-17: Partnerships for the goals; SDG-11: Sustainable cities and communities